2016
DOI: 10.1063/1.4964852
|View full text |Cite
|
Sign up to set email alerts
|

Laser-generated focused ultrasound for arbitrary waveforms

Abstract: Transducers for laser generated focused ultrasound can achieve photoacoustic waves with several hundred bars positive pressure in water. Previous designs employed concave glass substrates decorated with catalytically grown carbon nanotubes. Here, we show that arbitrarily shaped surfaces made of polymers and printed with 3d printers allow the generation of waveforms with complex temporal and spatial shape. We first present three different polymer materials together with a simplified deposition technique. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…(v) Focused ultrasound with complex temporal and spatial waveforms can be generated by utilizing arbitrarily shaped surfaces of polymers made by three-dimensional (3D) printing [72]. high-intensity and high-frequency LGUS focused transmitters [71].…”
Section: Focused Transmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…(v) Focused ultrasound with complex temporal and spatial waveforms can be generated by utilizing arbitrarily shaped surfaces of polymers made by three-dimensional (3D) printing [72]. high-intensity and high-frequency LGUS focused transmitters [71].…”
Section: Focused Transmittersmentioning
confidence: 99%
“…high-intensity and high-frequency LGUS focused transmitters [71]. (v) Focused ultrasound with complex temporal and spatial waveforms can be generated by utilizing arbitrarily shaped surfaces of polymers made by three-dimensional (3D) printing [72]. …”
Section: Focused Transmittersmentioning
confidence: 99%
“…Consequently, optical acoustic sources are ideally suited to broadband material characterisation [5] and detector calibration. In addition, optical ultrasound sources have been successfully applied to biomedical imaging [3], [6]- [8] and therapeutic settings [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The same work demonstrated that 3-D printing with transparent materials is well suited to the creation of these surface profiles. 10 The question of how to generate a desired acoustic field using different configurations of piezoelectric arrays has been addressed via optimisation in a number of previous works. 11,12 However, an approach has yet to be developed for the design of optoacoustic surface profiles.…”
mentioning
confidence: 99%
“…While not a focus of this work, it has been shown previously that the pressure can be increased up to MPa levels with appropriate design of the optical absorber. 10 The signal to noise ratio (SNR) in the target plane of the experimental data is 4.1. This was quantified by creating a mask encompassing the target pattern and calculating the ratio of the average peak pressure within the mask to outside it.…”
mentioning
confidence: 99%